A política de assistência estudantil no Instituto Federal de Educação, Ciência e Tecnologia de São Paulo: percepções de alunos sobre acesso e permanência - Norberto, Juliana Alvim (2020)
This study aims to discuss and analyze the Student Assistance Policy (SAP) at the Federal Institute of Education, Science and Technology of São Paulo (STSP), regulated by the National Student Assistance Program (NSAP), through Decree number 7,234, of July 19, 2010. It aims to identify potentialities and limits of the SAP for access and permanence of students enrolled in technical courses integrated to high school in 2019 academic year of the Advanced Campus São Miguel Paulista of STSP. Considering that it is a work developed in the Professional Master´s program for the Training of Educational Managers, it meets the objectives of the Program to contribute to the improvement of SAP´s action in order to implement the conditions of service to this student segment, preparing subsidies for the management of the Institute. The guiding questions of the study were: Do the criteria established in the institutional rules that regulate the Student Assistance Policy at STSP, favor the access and permanence of students who need this assistance policy? What are the students´ perceptions about their training process, originated from the Student Assistant Policy of STSP? In other words, the study discusses whether the STSP institutional rules used for the implementation of the SAP in 2011, until its consolidation as a Policy in 2014, meet the objectives proposed in the NSAP policy, through the perceptions of students in situations of social vulnerability. This is a qualitative study - inserted in the Research and Management of Education Research Group - which surveyed and analyzed the literature on the subject, discussed the legislation that regulates the Federal Network for Professional, Scientific and Technological Education and the NSAP and, next, analyzed documentary sources that regulate SAP in the STSP. Finally, to apprehend the students´ perceptions, used the focus group technique.